Attenuation of TNFSF10/TRAIL-induced apoptosis by an autophagic survival pathway involving TRAF2- and RIPK1/RIP1-mediated MAPK8/JNK activation - Weiyang He; Qiong Wang; Jennings Xu; Xiuling Xu; Mabel T. Padilla; Guosheng Ren; Xin Gou; Yong Lin (2012)
Although it is known that tumor necrosis factor-related apoptosis-inducing ligand (TNFSF10/TRAIL) induces autophagy, the mechanism by which autophagy is activated by TNFSF10 is still elusive. In this report, we show evidence that TRAF2- and RIPK1-mediated MAPK8/JNK activation is required for TNFSF10-induced cytoprotective autophagy. TNFSF10 activated autophagy rapidly in cancer cell lines derived from lung, bladder and prostate tumors. Blocking autophagy with either pharmacological inhibitors or siRNAs targeting the key autophagy factors BECN1/Beclin 1 or ATG7 effectively increased TNFSF10-induced apoptotic cytotoxicity, substantiating a cytoprotective role for TNFSF10-induced autophagy. Blocking MAPK8 but not NFκB effectively blocked autophagy, suggesting that MAPK8 is the main pathway for TNFSF10-induced autophagy. In addition, blocking MAPK8 effectively inhibited degradation of BCL2L1/Bcl-xL and reduction of the autophagy-suppressing BCL2L1-BECN1complex. Knockdown of TRAF2 or RIPK1 effectively suppressed TNFSF10-induced MAPK8 activation and autophagy. Furthermore, suppressing autophagy inhibited expression of antiapoptosis factors BIRC2/cIAP1, BIRC3/cIAP2, XIAP and CFLAR/c-FLIP and increased the formation of TNFSF10-induced death-inducing signaling complex (DISC). These results reveal a critical role for the MAPK8 activation pathway through TRAF2 and RIPK1 for TNFSF10-induced autophagy that blunts apoptosis in cancer cells. Thus, suppression of MAPK8-mediated autophagy could be utilized for sensitizing cancer cells to therapy with TNFSF10.